If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9n(5n + -1) = 0 Reorder the terms: -9n(-1 + 5n) = 0 (-1 * -9n + 5n * -9n) = 0 (9n + -45n2) = 0 Solving 9n + -45n2 = 0 Solving for variable 'n'. Factor out the Greatest Common Factor (GCF), '9n'. 9n(1 + -5n) = 0 Ignore the factor 9.Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0Subproblem 2
Set the factor '(1 + -5n)' equal to zero and attempt to solve: Simplifying 1 + -5n = 0 Solving 1 + -5n = 0 Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5n = 0 + -1 -5n = 0 + -1 Combine like terms: 0 + -1 = -1 -5n = -1 Divide each side by '-5'. n = 0.2 Simplifying n = 0.2Solution
n = {0, 0.2}
| 4(x-5)=96 | | 12(4x+5)-8x= | | 2.6q-2.6-2.8q=-1.2q-1.9 | | 3x+65+4x+40=180 | | 10x+12=4x-17 | | 35x^2+38x=-8 | | G(5a+1)=-3x+5 | | 2.6q-2.6-2.8q=1.2q-1.9 | | M=9/2 | | c^3/5 | | 2x=[2+(-10)]x+20 | | -2=j-2/5 | | 5.57-5/12 | | 276=-16t^2+20t+300 | | 4+4r=r-5 | | 5(x-2)+13(x+11)= | | 0.5x+0.6(x+2)=3 | | 6v/2v | | 74=8*q | | -5x^2+16x-9=0 | | 5-2(x-1)=4+x | | -[9x+(7x+15)]=11-(21x+9) | | 36r+21t-t-37= | | 7z^2-30z+7z^2=0 | | .25x-x=m | | 3p^2=0 | | 3r-5=-11+4r | | 2x^4+x^2-28=0 | | -4.2=7c | | 3.5x-x=m | | 46=7*q | | 2(6+2a)=-(2-4a) |